Employability within an Education for Sustainability Framework: The Ocean i3 Case Study - Olatz Zinkunegi-Goitia; Itziar Rekalde-Rodríguez (MDPI AG, 2022)
The Council of the European Union recalls that higher education plays a fundamental role in shaping the future of Europe. Therefore, curricula are required to take into account the competences demanded by the job market so that future workers can effectively undertake their professional activities and form part of an active, responsible, ecological, sustainable, and resilient society. Ocean i3 is a cross-border project with the aim of achieving sustainability in the oceans by training students to become environmentally concerned and responsible professionals. This study explores the perception of students and teachers regarding their participation in Ocean i3 and their understanding of employability. A qualitative methodological approach has been used, based on a case study in which semi-structured interviews have been carried out and the Elevator Pitch presentation technique has been applied. Nine students and four teachers from the University of the Basque Country and the University of Bordeaux have been interviewed. The results highlight the importance of the participants' first contact with the project, the need to be explicit regarding competences that favour employability during the development of the experience, and the need to increase and reinforce internships at social entities located in the territory. It is concluded that the project should focus more explicitly on the concept of employability to raise students' awareness of the impact that their current participation in Ocean i3 can have on their professional future and insertion in the workplace.